2009
DOI: 10.1002/ijc.24003
|View full text |Cite
|
Sign up to set email alerts
|

The methylenetetrahydrofolate reductase C677T mutation induces cell‐specific changes in genomic DNA methylation and uracil misincorporation: A possible molecular basis for the site‐specific cancer risk modification

Abstract: The C677T polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene is associated with a decreased risk of colon cancer although it may increase the risk of breast cancer. This polymorphism is associated with changes in intracellular folate cofactors, which may affect DNA methylation and synthesis via altered one-carbon transfer reactions. We investigated the effect of this mutation on DNA methylation and uracil misincorporation and its interaction with exogenous folate in further modulating these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 55 publications
4
68
0
Order By: Relevance
“…A reduced MTHFR activity, linked to the -677C4T polymorphism, could lead to an enhanced availability of non-methylated folate substrates for de novo synthesis of nucleotides, which could preserve DNA integrity, reducing uracil misincorporation, single-and double-strand breaks, DNA misrepair and genetic instability. 34 Patients with a wild MTHFR-677CC genotype could be more prone to DNA damage caused by ionizing radiation and thus be more sensitive to the therapy, though the effect of the polymorphism on ionizing radiation sensitivity appears to be related to micronutrients concentrations in vitro. 35 Further mechanistic studies are necessary to confirm this hypothesis and this predictive role of MTHFR-677C4T, as the others reported in this work should be interpreted with caution and further confirmed, because of the exploratory nature of the study.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced MTHFR activity, linked to the -677C4T polymorphism, could lead to an enhanced availability of non-methylated folate substrates for de novo synthesis of nucleotides, which could preserve DNA integrity, reducing uracil misincorporation, single-and double-strand breaks, DNA misrepair and genetic instability. 34 Patients with a wild MTHFR-677CC genotype could be more prone to DNA damage caused by ionizing radiation and thus be more sensitive to the therapy, though the effect of the polymorphism on ionizing radiation sensitivity appears to be related to micronutrients concentrations in vitro. 35 Further mechanistic studies are necessary to confirm this hypothesis and this predictive role of MTHFR-677C4T, as the others reported in this work should be interpreted with caution and further confirmed, because of the exploratory nature of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that human lymphoblasts with weaker MTHFR (homozygous of MTHFR C677T) have advantages in de novo purine synthesis when folate is adequate, but they are more susceptible to S-adenosyl methionine depletion when folate is restricted (21). In human colon and breast cancer cell models, MTHFR C677T mutation can induce cell-specific alterations in DNA methylation (33) as well as uracil incorporations into the DNA (34). Both are potential molecular bases for cell-or site-specific cancer risk modification.…”
Section: Gnmt Expression Induced Folatedependent Homocysteine Remethymentioning
confidence: 99%
“…[16][17][18] ECR is based on the measurement of the time variation of the electrical conductivity of the sample after a sudden change in the oxygen partial pressure at constant temperature. For mixed conductors, a change in the oxygen partial pressure results in a change in the charge carrier concentration that will result in a change in the electrical conductivity, which can be monitored experimentally during re-equilibration.…”
Section: Theoretical Considerationsmentioning
confidence: 99%